Characteristics and Persistence of Relict High‐Altitude Permafrost on Mahan Mountain, Loess Plateau, China - Changwei Xie; William A. Gough; Andrew Tam; Lin Zhao; Tonghua Wu (Permafrost and Periglacial Processes)
Mahan Mountain is the only region in the Loess Plateau (China) where permafrost persists. The permafrost is typical warm permafrost and remains in a very fragile and sensitive state. Remnants of permafrost (approximately 0.134 km2 in area) remain in a low‐lying swamp where the top 70 cm of soil contains abundant organic material (peat). The lowest temperature of the permafrost was ‐0.2°C between depths of 10 and 16 m, with temperature increasing upwards and downwards along a gradient of ± 0.01°C/m, and the permafrost thickness exceeded 30 m in this region. The distribution and thermal state of permafrost on Mahan Mountain closely relate to the surface conditions and soil type. In this study, the important protective effects of the peat layer and ground ice are illustrated using a one‐dimensional finite difference model of heat flow. The simulation results indicate that active‐layer thickness of permafrost on Mahan Mountain would increase by approximately 83 per cent under current climate conditions without the protection of the peat layer and ground ice. Based on the temperature projections of general circulation models, this study projects that permafrost will likely remain on Mahan Mountain for the next 40 to 50 years. Copyright © 2013 John Wiley & Sons, Ltd.